2010
DOI: 10.1103/physreve.82.031103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a polymer growth process with an equilibrium multicritical collapse phase transition: The meeting point of swollen, collapsed, and crystalline polymers

Abstract: We have investigated a polymer growth process on the triangular lattice where the configurations produced are self-avoiding trails. We show that the scaling behavior of this process is similar to the analogous process on the square lattice. However, while the square lattice process maps to the collapse transition of the canonical interacting self-avoiding trail (ISAT) model on that lattice, the process on the triangular lattice model does not map to the canonical equilibrium model. On the other hand, we show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 27 publications
11
47
1
Order By: Relevance
“…Interestingly, all these models k = 1,2,3 have been seen [14] to behave in the same way on the triangular lattice and, as we shall see, seem to behave in the same way on the simple cubic lattice (though the two-and three-dimensional models differ from each other in behavior).…”
Section: "Canonical" Isat Modelssupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, all these models k = 1,2,3 have been seen [14] to behave in the same way on the triangular lattice and, as we shall see, seem to behave in the same way on the simple cubic lattice (though the two-and three-dimensional models differ from each other in behavior).…”
Section: "Canonical" Isat Modelssupporting
confidence: 59%
“…The equivalent static model is an eISAT with a particular value of k = k G 4.15 at one particular temperature T = T G . It was demonstrated [14] that this value of k = k G separates models where the collapse transition is first order (k > k G ) from models where the collapse transition is second order (k < k G ). It was shown that for k < k G the second-order transition was most likely in a single universality class, which was the same as the one in the (two-dimensional) ISAW θ -point collapse transition.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this is quite different to the exponent ν = 4/7 for the ISAW. Another important difference that has been recently observed [29,30] is that the low temperature phase is maximally dense. On the square lattice this implies that if one considers the proportion of the sites on the trail that are at lattice sites which are not doubly occupied via…”
Section: Interacting Self-avoiding Trails (Isat)mentioning
confidence: 86%
“…By considering the trails on the triangular lattice we can assign different energies to doubly-or triply-visited sites, which induces another collapsed phase in two dimensions. The homogeneous lattice case of this model has been studied previously [20], showing that the collapse transition to the globule phase is θ-like and the other collapsed phase is characterised by maximally dense configurations whose interior is dominated by triply-visited sites. The important difference to the third phase of the semi-stiff ISAW model is that this maximally dense phase is not ordered in a real crystalline sense as so may behave differently to the introduction of disorder.…”
Section: Introductionmentioning
confidence: 99%